Faktor-faktor yang mempengaruhi kepuasan bekerja dalam kalangan pekerja sektor swasta: Kajian di Negeri Kedah Darulaman - Siti Nur Zahirah, Omar (2013)
This study aims to look at the issue of the level of job satisfaction among private sector workers in the Kedah State. The main objective of this study was to identify any relationship between pay, supervision, the work itself, work conditions, opportunities for promotion and job satisfaction. This study was conducted using quantitative methods of data were collected using a set of questionnaires. Books questionnaire was used to obtain feedback from respondents. The study sample consisted of employees of private sector workers in the Kedah State which has a total of 500 respondents participated in this study. The findings showed that there is a positive relationship between pay, supervision, the work itself, work conditions, opportunities for promotion and job satisfaction. This indicates that satisfied employees working in their respective organizations. This study has provided a better understanding of the factors that influence job satisfaction in the private sector. Results of this study provide benefits to private organizations, particularly the management in knowing and measuring the level of satisfaction of their employees